Analysis of etiology and antimicrobial sensitivity of fungal keratitis pathogens in a series of clinical cases - A. N. Samoylov; N. I. Davletshina (Офтальмохирургия, 2020)
Purpose. To analyze pathogens of keratomycosis resistant to antifungal therapy, the spectrum of sensitivity to antimicotic agents in series of fungal keratitis. Material and methods. There is a retrospective analysis of fungal keratitis in 12 patients (12 eyes) who underwent an inpatient treatment from August 2018 to January 2020 (18 months). Clinical data of patients was recorded in specially developed forms. Results.Keratomycosis was confirmed in 12 cases of keratitis with resistantce to the local antimicrobial and anti-inflammatory therapy during the study period. All patients used contact lenses from different manufacturers, had a history of outpatient treatment with antibacterial, non-steroidal anti-inflammatory eye drops, and keratoprotectors, topical glucocorticosteroids and antiherpetics for 2 weeks to 2 months. Identification of the pathogen was carried out by the direct microscopy method, followed cultural research in the mycological laboratory, as well as clinical manifestations. In 10 cases, Fusarium spp was detected, in 1 case – Penicillinum, in 1 case – Candida. According to the conclusion of the mycological study, 100% of fungal agents has resistance to fluconazole and amphotericin B. The sensitivity of agents to antimicotic agents was analyzed, and the equipment of antifungal drugs required for use on the basis of the study was revised. Conclusion. In a series of clinical cases of fungal keratitis, the dominant pathogen was Fuzarium. The found broad resistance to fluconazole and amphotericin B, high sensitivity to nystatin, terbinafine, and ketoconazole shows that each case of keratomycosis has an original clinical picture, must be considered in detail, and requires a careful diagnosis and individual treatment tactics.